Eksplorasi Pemikiran Abu Ma’shar Al Falaky Tentang Manuasia dan Bintang - Fikri, Mursyid; Syarif, Muh Rasywan (ELFALAKY: Jurnal Ilmu Falak, 2019)
AbstractOf the many sciences that once recognized his belief in giving color to the life of Islam, one of them is the science of astrology. One of the great scholars who introduced the widespread science of astrology was abu ma'shar Al-falaky, the title of al-falaky given to him because of his greatness in connecting natural events with human life. Therefore this paper will discuss some of the thought of abu ma'shar al-falaky in ash book ma'shar Alfalaky which discussed 14 chapters then the author tries to peel 4 chapters between the chapters namely lesson losing chapter, chapter year, ill-fitting article and article human relationship with the star. By combining with scientific studies.            Key Words : Abu Ma’Shar,thought,  Astrology